Análisis de modelos de gestión del conocimiento - Fernando Rodríguez-Fonseca; Hugo Fernando Castro-Silva; César Augusto Dávila- Carrillo (Mundo Fesc)
Within the academic literature, there are different models for managing knowledge, both empirically and theoretically, which demonstrate diverse ways of creating, capturing, disseminating, and applying knowledge as a fundamental basis for the development of any type of organization. However, some inconsistencies and gaps were identified in the models for managing knowledge in organizations. The purpose of this research is to analyze the different knowledge management models, both applied to organizations and theoretically, based on the background of this area of ​​knowledge. The methodology used consisted of a systematic literature review in bibliographic databases. It was concluded that a knowledge management model must take into account the specific practices of each organization and implement stages that promote greater learning, innovation, and participation among collaborators, with the aim of generating value and competitive advantages for the organization